Sintesis Katalis Kalsium Gliseroksida Berbasis Cangkang Telur Bebek-Crude Glycerol dan Aplikasinya dalam Transesterifikasi Minyak Sawit untuk Produksi Biodiesel - Surya Alam, Widharta; Gitamara, Sabila; Masyithah, Zuhrina (Jurnal Teknik Kimia USU, 2022)
The growth of biodiesel production resulted in an increase in by-products in the form of crude glycerol. To increase its economic value, crude glycerol can be further processed into heterogeneous catalysts. The reaction between glycerol and calcium from duck eggshell will produce calcium glyceroxide which is useful in transesterification. In this study, catalyst preparation was carried out by reacting crude glycerol with calcined duck eggshell (700 °C) at a ratio of (1:1) (g) refluxed in methanol solvent. The obtained catalyst was applied to palm oil transesterification at mole ratio (1:12), catalyst concentration 0.4%; 0.7% and 1% (w/w), operating temperatures of 55 °C, 65 °C and 75 °C for 75 minutes. KOH is also used as a comparison catalyst. The analysis of SNI 7182-2015 includes density (40 °C), viscosity (ASTM D-445), acid number (AOCs Cd 3-63), and water content (ASTM D-2709). The optimum conditions according to SNI 7182-2015 are at a temperature of 65 °C and 0.7% catalyst with biodiesel yield of 88.76%, density 889 kg/m3, kinematic viscosity 5.1 mm/s2, acid number 0.5 mg KOH/g and moisture content of 0.0028%.